STUDI PENGARUH PEMASANGAN SPIKE UNTUK MELINDUNGI SALURAN DISTRIBUSI TEGANGAN MENENGAH PADA PENYULANG BUDUK - Dodik Darma Putra, I Kadek; I Gede Dyana Arjana, I Gede Dyana Arjana; Rinas, I Wayan (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUM, 2021)
Buduk feeder is a 20 Kv medium voltage distribution system that gets power supply from the ship's substation and crosses large coastal areas and rice fields and is prone to natural phenomena such as lightning. During 2018 there were 3 lightning disturbances. Based on these data, it is necessary to analyze the distribution channel failure at Buduk feeders, so the continuity of the distribution channel can be better. The performance of the Spike System is when a lightning surge occurs on the distribution channel, the Spike System directly transmits the lightning strike to the ground. Based on the data analysis, it is necessary to add a Spike protection system to the Buduk Feeder to maintain the continuity of electric power.The method used in this research is to collect data in the form of a single line diagram, disturbance data due to lightning strikes at Buduk feeders. Next, compared the Buduk feed line before Spike installation and after spike installation. First, analysis of technical data and the channel performance before spike installation. Second, proceed with channel analysis after the installation of the Spike. Third, to analyze the causes of failure due to lightning strikes on the feeders. The results obtained after the installation of the Spike system, the number of disturbances due to lightning surges, both induction and direct strikes, decreased in 2019 with the number of interruptions one time.